Avaliação e modelagem de colapso em madeiras de Eucalyptus grandis - Souza, Poliane Pereira de (2018)
Wood drying is a fundamental step for its use in various purposes, however, drying is a difficult process for some species such as Eucalyptus grandis. The defects from wood drying are common in this specias with collapse as one of the major defects occurring during drying. Detailed information about this defect are scarce in the current literature. Therefore, it is justified to carry study collapse, since it is a defect with a large occurrence and that depreciates wood quality. This study is divided into chapters to explore as much information as possible about the defect in question. Chapter I presents a brief theoretical discussion about the main characteristics of the collapse. This chapter also discusses the main themes related to its occurrence: water movement in wood, drying, defects, permeability. Chapter II includes the physical and anatomical characterization of wood, the evaluation of collapse index and its correlations. The anatomical characteristics presented values within intervals characteristic of the species. The collapse index was considered strong for the studied trees and showed poor correlation with basic density, fiber width and vessel length. Chapter III proposes the collapse modeling as well as to obtain the curve of the humidity as a function of the time of drying and collapse curve, both during the exit of free water of the wood. From a logistic model with four parameters, estimation of area loss was possible by collapse and the critical point of deformation for each position. The samples that presented greater deformations due to collapse were those closer to the marrow of the trees. The critical point of collapse in the wood of Eucalyptus grandis was at 225 minutes, witch points to the need for caution that must exist in the first hours of drying for this species.